Five Areas Which Make the Irish Organized Crime Milieu Distinctive - Windle, James (Journal of contemporary criminal justice, 2023)
This article critically assesses five areas that may together make the Irish organized crime milieu distinctive. First, there is minimal research. Second, organized crime groups and illicit enterprises are often characterized as “family-gangs.” Third, some violent conflicts are framed as family feuds. Fourth, a broad range of paramilitary groups have influenced Irish organized crime, in a variety of ways. Fifth, many organized crime groups and illicit enterprises are internationally mobile. Three types of mobility are identified: those commuting to other countries for one-off jobs, those migrating for longer periods, and mobile illicit enterprises. Allum’s push/pull model of criminal migration is employed to offer some suggestions as to why Irish criminals migrate and the choice of destination. The final section argues that some of the features that make Irish organized crime distinctive are changing or may have already changed. The article highlights key areas of further research needed to clarify the structure of organized crime in Ireland.